Increased circulating microparticles in women with preeclampsia. (9th March 2018) - Zhang, Y.; Zhao, C.; Wei, Y.; Yang, S.; Cui, C.; Yang, J.; Zhang, J.; Qiao, R.
Abstract: Introduction: Preeclampsia (PE) is associated with hypercoagulability, endothelial dysfunction and inflammation, which generate microparticles (MPs). Therefore, MPs may be important for PE. Methods: We established a verified MP measurement procedure to detect MPs in nonpregnant women (n = 25), healthy pregnant women (n = 29) and PE women (n = 73) and compared their MP levels. Results: Microparticles prepared from platelets (PMPs), endothelial cells (EMPs) and leucocytes (LMPs) were confirmed by transmission electron microscopy and were analysed by our established flow cytofluorimetric approach, which showed good specificity for determining the cell origin and level of MPs. The levels of total MPs (tMPs) and PMPs in the healthy pregnant group were significantly higher than those in the nonpregnant group (158.78 vs 93.00 and 45.04 vs 17.41, P  = .004 and P  = .007, respectively) but were not significantly different from those of the PE group. However, EMPs and LMPs were significantly higher in the PE group than in the healthy pregnant group (14.62 vs 11.48 and 8.94 vs 5.03, P  = .015 and P  < .001, respectively). Furthermore, the area under the receiver operating characteristic curves (AUC) for EMPs, LMPs and the combined sum of EMPs and LMPs were 0.661, 0.746 and 0.718, respectively ( P  < . 05); at their optimal cut‐off values, the sensitivities were 50.68%, 87.67% and 46.58%, respectively, and the specificities were 80.77%, 58.33% and 95.65%, respectively. Conclusion: Determining the MP level, especially that of EMPs and LMPs, by a specificity‐verified method may reflect the endothelial dysfunction and inflammation involved in PE pathogenesis.